Peningkatan Literasi Anak dan Pemberdayaan Perempuan Melalui Forum Edukasi Keluarga dalam Perspektif Desa Ramah Perempuan dan Anak - Palal, Ghaza Juliet; Sallimah, Durratul Fuadatus; Mayanti, Aldila Dwi; Tansania, Rita; Amin, Mohammad; Azim, Hafidz Afrizal; Sutini (JATIMAS : Jurnal Pertanian dan Pengabdian Masyarakat, 2025)
This article discusses efforts to improve child literacy and empower women through the establishment of a Family Education Forum (FEK) using a participatory approach in Sidorejo Village, as part of implementing a child- and women-friendly village model. The background of this community service is the limited access to informal education at the family level, minimal involvement of mothers in their children's home learning, and the absence of a forum that integrates family-based education. The community engagement employed the Participatory Action Research (PAR) method, comprising stages that included problem mapping, program planning, forum implementation, and participatory evaluation. The results show that FEK effectively improves children's basic literacy and strengthens the role of women in family decision-making. The forum also becomes a productive communication medium among family members and the village community. The novelty of this research lies in the integration of family education, children’s literacy, and women’s empowerment into a single, sustainable, and participatory platform, unlike conventional family literacy models that focus solely on children’s cognitive aspects. This article concludes that the family education forum model has great potential in developing an inclusive and sustainable community-based education support system. Artikel ini membahas tentang upaya peningkatan literasi anak dan pemberdayaan perempuan melalui pembentukan Forum Edukasi Keluarga (FEK) berbasis pendekatan partisipatif di Desa Sidorejo sebagai bentuk implementasi desa ramah perempuan dan anak. Latar belakang kegiatan ini adalah rendahnya akses edukasi nonformal di tingkat keluarga, minimnya peran ibu dalam pembelajaran anak di rumah, serta belum adanya forum yang mengintegrasikan edukasi berbasis keluarga. Kegiatan pengabdian menggunakan metode Participatory Action Research (PAR), dengan tahapan pemetaan masalah, perencanaan program, implementasi forum edukasi, serta evaluasi bersama mitra. Hasil menunjukkan bahwa FEK mampu meningkatkan literasi dasar anak dan memperkuat peran perempuan dalam pengambilan keputusan keluarga. Forum ini juga menjadi sarana komunikasi produktif antaranggota keluarga dan komunitas desa. Kebaruan penelitian ini terletak pada integrasi pendidikan keluarga, literasi anak, dan pemberdayaan perempuan dalam satu wadah partisipatif yang berkelanjutan, berbeda dengan model literasi keluarga konvensional yang hanya berfokus pada aspek kognitif anak. Artikel ini menyimpulkan bahwa model forum edukasi keluarga memiliki potensi besar dalam membangun sistem pendukung pendidikan berbasis komunitas yang inklusif dan berkelanjutan.